Qualitative Comparison of Barriers to Antiretroviral Medication Adherence Among Perinatally and Behaviorally HIV-Infected Youth. (July 2017) - Fields, Errol L.; Bogart, Laura M.; Thurston, Idia B.; Hu, Caroline H.; Skeer, Margie R.; Safren, Steven A.; Mimiaga, Matthew J.
Medication adherence among youth living with HIV (28%–69%) is often insufficient for viral suppression. The psychosocial context of adherence barriers is complex. We sought to qualitatively understand adherence barriers among behaviorally infected and perinatally infected youth and develop an intervention specific to their needs. We conducted in-depth interviews with 30 youth living with HIV (aged 14–24 years) and analyzed transcripts using the constant comparative method. Barriers were influenced by clinical and psychosocial factors. Perinatally infected youth barriers included reactance, complicated regimens, HIV fatigue, and difficulty transitioning to autonomous care. Behaviorally infected youth barriers included HIV-related shame and difficulty initiating medication. Both groups reported low risk perception, medication as a reminder of HIV, and nondisclosure, but described different contexts to these common barriers. Common and unique barriers emerged for behaviorally infected and perinatally infected youth reflecting varying HIV experiences and psychosocial contexts. We developed a customizable intervention addressing identified barriers and their psychosocial antecedents.